Conversion of Indonesian Coal Fly Ash into Zeolites for Ammonium Adsorption - Prihastuti, Hesti; Kurniawan, Teguh (Bumi Publikasi Nusantara, 2022)
The synthesis of zeolite from fly ash has been investigated. The method used for the synthesis of zeolite in this research is the smelting method followed by a hydrothermal process. The zeolite synthesis was characterized using XRD and SEM. Based on the research results, it was found that fly ash can be synthesized into Na-P zeolite with morphology like coral, and cancrinite zeolite and sodalite with morphology like seaweed. The optimum condition for zeolite synthesis occurred at a hydrothermal process at 160°C for 24 hours with the formation of cancrinite zeolite. The synthesized zeolite resulting from the separation of 4 M of HCl formed Na-P zeolite and silica phase crystals which had the most optimum absorption of ammonium with an adsorption capacity of 18.025 mg/g with the adsorption kinetics model in the form of pseudo-second-order with a constant rate of 0.557 h-1 .